Assessing Validity and Reliability of Muslim Student’ Interpersonal Communication Scale: A Rasch Model Study - Widyastuti, Dian Ari; Purwanta, Edi; Astuti, Budi; Izzaty, Rita Eka; Farozin, Moh; Ismail, Affero; Naini, Rohmatus (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
Developing a scale of interpersonal communication for Muslim students in Indonesia is very important because of the unique cultural and religious context that these students live in. Effective interpersonal communication is essential to fostering a supportive educational environment, improving peer relationships, and improving students' overall well-being. Currently there are no published research findings that specifically discuss measuring interpersonal communication among Muslim students in Indonesia. Therefore, this research aims to develop a valid and reliable Muslim Student Interpersonal Communication Scale (MSICS). MSICS was developed based on five aspects: openness, empathy, supportiveness, positivity, and equality. Content validity was assessed by two psychometric experts, and the results were analyzed using an inter-rater agreement model. Construct validity involved 432 Muslim junior high school students in Yogyakarta City, Indonesia, and the data was analyzed using the Rasch model. The results of the interrater agreement model analysis show that there is agreement between two psychometric experts regarding the acceptability of the statement items in the MSICS. Furthermore, the Rasch model analysis shows that the MSICS appears as a valid and reliable instrument for assessing the level of interpersonal communication among Muslim students in junior high schools in Indonesia with a variance explained by measures value of 26,7% (>20%), which means good enough to describe the measured data, and the reliability value is 0,91, which means very good. The results of this research can be used by counselors or guidance and counseling teachers to use MSICS as an instrument to measure Muslim students' interpersonal communication.